"That's a double-edged sword": Exploring the integration of supervised consumption services within community health centres in Toronto, Canada. (January 2020) - Bardwell, Geoff; Strike, Carol; Mitra, Sanjana; Scheim, Ayden; Barnaby, Lorraine; Altenberg, Jason; Kerr, Thomas
Abstract: Supervised consumption services (SCS) have been integrated into community health centres in Toronto. We draw on qualitative interviews and ethnographic observations to examine the implementation contexts of these SCS. Participants' perspectives on the integration of SCS within CHCs were mixed. Some participants identified the benefits of integrated SCS such as convenience and access to other health and social services. However, others identified negative consequences of integration, including building design, lack of privacy and anonymity, and limited hours of operation. These perspectives highlight the ways in which contextual factors affect the experiences of clients in accessing SCS, and suggest that various factors need to be considered in order to improve service uptake. Highlights: Integrating SCS within health centres provided clients access other health services. Hours of operation were seen as a barrier to SCS service uptake. The building layouts created privacy and anonymity concerns for clients.